Estratégia Saúde da Família e internações por condições sensíveis a atenção ambulatorial : relação produzida no campo da prática profissional - Birchler, Célia Márcia (2007)
The Family Health, which is the object of the present study, while Strategy of organization of the Primary Attention to Health, has been consolidated as an entry door for the assistant services in an adscript territory. Nevertheless, several challenges permeate its trajectory in the state of Espírito Santo, aiming at: evaluating the Family Health Strategy in the micro region of Guaçuí; analyzing the tendencies of CSAA internments of five-year old children from 2000 to 2005 and; analyzing how the Family Health project teams are organized in order to create strategies which cause impacts in the CSAA internments. The definition by Guaçuí micro region as a research scenery is made due to its 100% population covering in the Strategy, providing the correlation with the study of the internments by sensitive conditions to the ambulatory attention (CSAA), the indicator. Because of the complexity of the factors that involve objects and objectives, working with the triangulation of techniques that have been completing throughout the study was the best option. It is about a descriptive study of qualitative approach that incorporates a quantitative component statistically analyzed and qualitative components approached with the use of analyzing flux gram and group interview. The results show the gastroenteritis as the main cause of internment of five-year old children. The result inserted the debate about the social determinants and its influence in the process of getting ill. The field research added subsidies for the analysis, making possible the verification of the lack of strategies aimed at the following of that grievance, the fragility of the vinculums together with the population and the necessity to implement public policies that go beyond the health sector.